2018
DOI: 10.3389/fmicb.2018.01240
|View full text |Cite
|
Sign up to set email alerts
|

An Antimicrobial Peptide Induces FIG1-Dependent Cell Death During Cell Cycle Arrest in Yeast

Abstract: Although most antibiotics act on cells that are actively dividing and non-dividing cells such as in microbe sporulation or cancer stem cells represent a new paradigm for the control of disease. In addition to their relevance to health, such antibiotics may promote our understanding of the relationship between the cell cycle and cell death. No antibiotic specifically acting on microbial cells arrested in their cell cycle has been identified until the present time. In this study we used an antimicrobial peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Thus, IP-1 toxicity does not involve mitochondrial function. In agreement with this idea, we have shown that IP-1 kills yeast cells lacking mitochondria DNA [ 27 ] and more recently reported that IP-1 kills yeast cells grown in either respiratory (mitochondria competent) or fermenting (mitochondria incompetent) media [ 51 ].…”
Section: Discussionsupporting
confidence: 64%
“…Thus, IP-1 toxicity does not involve mitochondrial function. In agreement with this idea, we have shown that IP-1 kills yeast cells lacking mitochondria DNA [ 27 ] and more recently reported that IP-1 kills yeast cells grown in either respiratory (mitochondria competent) or fermenting (mitochondria incompetent) media [ 51 ].…”
Section: Discussionsupporting
confidence: 64%
“…However, if NLS-α-CE and chimera peptides would be disrupting the membrane potential of MATa cells as part of their toxicity, we would expect these peptides to penetrate more easily these cells than the α-NLS-C peptide, which is the opposite of what we observed, hence the observed reduced internalization of NLS-α-CE and chimera peptides may not be explained by the toxicity reported for these peptides. On the other hand, we have reported that modifying the C-terminus region of the pheromone reduces its activity in a moonlighting peptide [ 13 ]. The NLS-α-CE is the only peptide that did not modify the C-terminus region of the pheromone and consequently we would not expect this peptide to reduce its affinity for its receptor, while the α-NLS-C and chimera peptides did, providing a possible explanation for their reduced ability to selectively penetrate MATa cells.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted a previous protocol reported to analyze fluorescent single yeast cells [ 13 ]. Briefly, cells were grown overnight and diluted to a final optical density measured at 600 nm of 1.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain the directionality of the growth, the influx of calcium ions is necessary [ 96 ], and this is where Fig1 is recruited for regulating calcium ion uptake at sites of polarized tip growth [ 90 ] to enhance membrane stability during morphological transitions. Deletion of Fig1 gene leads to significantly reduced ability of hyphal tips to reorient upon contact with ridges, but it does not affect Ca 2+ uptake during vegetative growth [ 97 , 98 ].…”
Section: Alkali and Alkali Earth Metalsmentioning
confidence: 99%